A quasi-experimental study of the volume-based procurement (VBP) effect on antiviral medications of hepatitis B virus in China - Wen, Xiaotong; Xu, Luxinyi; Chen, Xiaoze; Wu, Ruonan; Luo, Jia; Wan, Yuying; Mao, Zongfu (Frontiers in Pharmacology, 2023)
Background: The Pilot Plan of National Centralized Volume-Based Procurement (NCVBP) was adopted to cope with the rapid increase in drug expenditures. This research aimed to quantitatively evaluate the impact of the NCVBP on antiviral medications for the hepatitis B virus. Methods: Data on nucleoside analogs (NAs) medications of hepatitis B virus monthly procurement records in the pilot cities from January 2018 to December 2019 were extracted from the China Drug Supply Information Platform (CDSIP). The impacts of the NCVBP on purchased volumes, expenditures, and pre-defined daily dose costs were evaluated by interrupted time-series (ITS) analysis using Stata 16.0. We constructed two segments with one interruptive point (March 2019). Results: Compared to the same period between pre-and post-intervention, the purchased volume of NAs medications were increased by 92.85%, and selected medications were increased by 119.09%. Analysis of changes in the level of NAs medication followed a decrease in purchased expenditure (coefficient: 5364.88, p < 0.001), meanwhile, the purchased volume was increased with statistical significance (coefficient:605.49, p < 0.001). The Defined Daily Dose cost (DDDc) of NAs medication followed a decrease (coefficient: 8.90, p < 0.001). The NCVBP reform was followed by an increase of 618.41 ten thousand Defined Daily Dose (DDD) (p < 0.001) in purchased volume and a reduction of 5273.84 ten thousand Chinese Yuan (CNY) (p < 0.001) in the purchased expenditure of selected medications in the level. The DDDc of selected medications decreased in the level (coefficient: 9.87, p < 0.001), while the DDDc of alternative medications increased in the slope (coefficient:0.07, p = 0.030). The purchased volume and expenditure of bid-winning products increased by 964.08 ten thousand DDD and 637.36 ten thousand CNY in the level (p < 0.001). An increase of 633.46 ten thousand DDD (p < 0.001) in purchased volume and a reduction of 4285.32 ten thousand CNY (p < 0.001) in the purchased expenditure of generic drugs in the level was observed. Conclusion: The NCVBP reduced the DDDc of NAs medication, improved the utilization of the selected medications, and promoted the usage of generic products.